Effect of MRSA Irradiation by 632, 532, and 405 nm (Red, Blue, and Green) Diode Lasers on Antibiotic Susceptibility Tests - Ali, Ayat M. (Journal of the Faculty of Medicine Baghdad, 2017)
Background: Since the discovery of penicillin and till now, antibiotics are considered the most important regime in treating bacterial infections, insipid the fast development of bacterial resistance to many antibiotics over decades. Methicillin resistance Staphylococcus aureus (MRSA) is one of these bacteria types that emerged resistance to all current antibiotic classes. Fortunately, many studies proved phototherapy as a promising supporting to antibiotics in clinical fields.Objectives: The purpose of this study is to evaluate the effect of three lasers wavelengths (red, blue, and green) with 50 mW power density on the susceptibility of clinical MRSA isolates.Materials and methods: 45 clinical identified MRSA isolates are exposed to 632, 532, and 405 nm (red, blue, and green) Diode lasers. The susceptibility tests with 12 antibiotics are determined by disk diffusion method and minimum inhibition concentration (MIC) tests.Results: The results demonstrate an increasing in the clear zone of antibiotics for all the isolates, especially for the red wavelength which was more effective, rather than the blue and green lasers which come next respectively. The effective inhibition doses of the antibiotics are decreased for lasered MRSA. The red wavelength is again more effective than the two others lasers.Conclusion: the visible laser wavelength (red, blue, and green) improved the in vitro action of the antibiotics against MRSA.